Evaluating the causal contribution of fronto-parietal cortices to the control of the bottom-up and top-down visual attention using fMRI-guided TMS. (May 2020) - Wang, Min; Yu, Banglei; Luo, Cimei; Fogelson, Noa; Zhang, Junjun; Jin, Zhenlan; Li, Ling
Abstract: Previous studies demonstrate that frontal and parietal cortices are involved in bottom-up and top-down attentional processes. However, their respective contribution to these processes remains controversial. The purpose of the current study was to compare the causal contribution of frontal and parietal cortices to the control of bottom-up and top-down visual attention using functional magnetic resonance imaging (fMRI) and repetitive transcranial magnetic stimulation (rTMS). Subjects performed visual search for targets that were easy (pop-out) or difficult (non-pop-out) to distinguish from distractors. Three sites of interest were used, based on the individual fMRI activation during the performance of a search task: the right dorsolateral prefrontal cortex (rDLPFC), the right frontal eye field (rFEF) and the right superior parietal lobule (rSPL). Online rTMS stimulation, with the search onset, showed that relative to rTMS over the vertex, rTMS over the rDLPFC, the rFEF and the rSPL increased the search reaction time (RTs) in the non-pop-out condition. In comparison, no TMS effect was found in the pop-out condition. In addition, the search RT cost caused by the non-pop-out condition was larger after the rDLPFC-TMS compared to the vertex-TMS. The findings suggest that the frontal and parietal cortical regions are both involved in attentional processing during top-down visual search, and that the rDLPFC is causally related to the executive control of cognitive load increases between the pop-out and the non-pop-out search.